Interventions and strategies to prevent catheter‐associated urinary tract infections with short‐term indwelling urinary catheters in hospitalized patients: An integrative review. Issue 3 (13th March 2020) - Yu, Shuhui; Marshall, Andrea P.; Li, Jing; Lin, Frances
Abstract: Aim: To explore interventions and strategies to prevent catheter‐associated urinary tract infections in hospitalized patients with a short‐term indwelling urinary catheter. Background: Interventions and strategies to prevent catheter‐associated urinary tract infections are reported in the literature, but it is not clear which might be relevant when the indwelling urinary catheter is in place for a short period of time. Methods: An integrative review was performed. A search was undertaken in databases using the following search terms: "urinary catheter, bladder catheter OR urethral catheter*"and "bundl* OR care OR manag* OR intervent*." Electronic databases were searched up until June 2019. Manual searching of reference lists of included studies was undertaken. Twelve studies reported in 15 articles were identified and analysed by two independent reviewers. Results: Multifaceted interventions were informed by evidence‐based protocols or guidelines. Implementation strategies included local adaption of guidelines or protocols, use of an opinion leader, audit and feedback, multidisciplinary team involvement, reminders and stop orders, and education and training. Conclusion: Multifaceted, evidence‐based interventions to prevent catheter‐associated urinary tract infections are effective in preventing infections in patients with short‐term urinary catheters. However, there is little evidence to inform which combined strategies are more likely to be effective. SUMMARY STATEMENT: What is already known about this topic? Research suggests that multiple interventions and strategies might be helpful in preventing catheter‐associated urinary tract infections, particularly for long‐term catheterization. What this paper adds? In the context of short‐term urinary catheterization, evidence‐based strategies that could assist in reducing catheter‐associated urinary tract infections are available. A variety of strategies could be effective in implementing guidelines, including local adaptation of guidelines, use of opinion leaders, audit and feedback, and using reminders; however, these are poorly described in the current literature. The implications of this paper: Multifaceted interventions can be effective in preventing catheter‐associated urinary tract infections in patients with short‐term urinary catheters across variable settings. Strategies to best implement these interventions require further investigation but should be tailored to the local context.